Getting to Know Library Users’ Needs — Experimental Ways to User-centred Library Innovation - Harbo, Karen; Vibjerg Hansen, Thomas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
‘Meeting the User’ is a programme committee under the Danish Electronic Research Library. As a development group at a national level we see our role as facilitating an innovative culture within academic libraries, focusing on users’ needs and the way libraries meet them. In collaboration with a consultancy firm, the committee organized a travelling workshop in four cities in 2010. The workshop introduced practical ways for library staff to get to know their users’ needs for services and was based on anthropological methods. The travelling workshop was part of a larger project called ‘A Journey of Discovery in Danish Library User Land’ (translated from Danish Brugerkaravanen), which also included a national thematic day, a blog and the publication of a method guide. There is an ongoing need for academic libraries to improve their services. One strategy is to become more aware of the users’ needs. On the one hand we have libraries which give access to a lot of information, offer courses in information literacy and strive to be a part of the learning environment. On the other hand we are not always certain of the needs of our users. If libraries want to improve the way they serve their users’ needs, they must innovate their services, facilities and courses by building upon what you could call ‘user logic’ and not upon classical ‘library logic’. ‘User logic’ is that which is meaningful for the user instead of what is traditionally meaningful for a library. Finding out what the users’ needs are, requires methods to study the users. In order to discover the shortest route from knowledge via idea to action, we looked for methods that can be employed by librarians or library information specialists. This article describes how 110 librarians and information specialists acquired such methods in four cities and in four days, by means of a workshop structured like a guided tour through the land of library users. The goal of the article is to give other libraries inspiration for ideas, concepts and concrete tools to study user behaviour and become more aware of the user’s needs for service. The article contains a description of the above-mentioned methods, valuable experiences from the workshop, a presentation of the concept and concrete tools, discussion of the concept of user logic and library services, and the seven principles for human-centred innovation in relation to libraries, a short list of studies carried out by librarians and discussion of further perspectives.